Evolution of the Holuhraun fissure eruption (Bardarbunga Volcano, Iceland 2014) monitored by multi-sensor and multi-temporal remote sensing data - Plank, Simon; Fuchs, Eva-Maria; Martinis, Sandro; Twele, André (2015)
The Holuhraun fissure eruption, a dike intrusion originated at the Bardarbunga Volcano, is one of the largest eruptions in modern Icelandic history. Increasing seismic activity from 16 August 2014 onwards signalized the development of the dike, which broke through the Earth’s surface on 29 August 2014. By mid of January 2015 the fissure has extended to a length of over 18 km. An area of approx. 84 km² has been covered by lava. By using multi-sensor and multi-temporal Earth observation datasets the evolution of the fissure eruption was monitored over a time period of five months. The datasets contain time series of multispectral imagery from low (MODIS), to high (Landsat-8) and very high spatial resolution (WorldView-2 and -3) as well as data of synthetic aperture radar (SAR) missions (TerraSAR-X and Sentinel-1). On a daily basis MODIS provides information about the thermal activity at low spatial resolution, whereas Landsat-8 enables a more detailed analysis of the lava coverage and thermal activity using its visible, near infrared and thermal channels (16-days repeat cycle). In addition, selected acquisitions of WorldView-2 and -3 are used for very detailed investigations of the development of the lava coverage. As radar waves are able to penetrate atmospheric clouds and volcanic ash plumes, imagery from SAR sensors have been successfully applied for monitoring the development of the lava coverage. Therefore, a series of TerraSAR-X and Sentinel-1 acquisitions are used to guarantee a continuous and frequent monitoring of the temporal evolution of the fissure eruption. The results achieved in this study are in accordance with the reports of the Icelandic Meteorological Office (http://en.vedur.is/earthquakes-and-volcanism), which are based on ground survey and airborne data.